URGENSI KETELADANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAK SISWA - Zainal Azman (El-Ghiroh : Jurnal Studi Keislaman, 2018)
Education with keteladan means educational process that provides more examples, whether in the form of behavior, nature, way of thinking and so forth. The tendency of students to learn by imitating causes exemplary becomes very important in the process of education, it is because in learning the students in general easier to catch the concrete rather than the abstract. Basically the human need for exemplary figures stems from the tendency to imitate the already human character. This imitation centers on three elements of imitation, imitation and imitation. In behavior, imitating is essential, in the fact that certain individuals and communities mimic with consciousness, what they intend to imitate is thought rationally and profoundly so as not to fall into error. There is also a mimic not with consciousness will usually be wild uncontrolled even impressed can not choose.